Analysis of the conditions of application of flow converters and means of measuring gas flow parameters in the information and measurement system of gas accounting - Yu.O. Podchashinskiy; L.O. Chepiuk; T.S. Voronova; L.Yо. Shavurska (Технічна інженерія)
Improvement of accounting of gas consumption can be achieved due to the widespread use of information and measurement systems. Thanks to the improvement of methods and means of measurement, the ultrasonic method of measurement is promising. It has the following advantages: non-contact measurement of various types of substances, high reliability of primary transducers, absence of moving parts, practically unlimited range of measurements, high accuracy. This article discusses the conditions for using ultrasonic flow transducers, a calculator, and means of measuring gas flow parameters. The following measuring tools and technical devices are generally used to measure the flow rate and amount of natural gas: ultrasonic flow transducer; means of measuring gas flow parameters (temperature, pressure, density, component composition); devices for processing output data of measuring channels and calculating gas flow and quantity; connecting lines and auxiliary devices (filters, jet straighteners, etc.). The requirements for the measured medium and the measuring pipeline are determined. Measurement tools and requirements for their installation are given.